Assessment of Mental Health in Doctor of Pharmacy Students In India - A Survey - Barath Raj. R,; Keshavini. S,; Jagadheeshwari. M,; Afrin Baig,; Leena Muppa,; Nithya Sri Pandi, (International Journal of Scientific Research in Science and Technology, 2025)
Background: Mental wellbeing is crucial for Doctor of Pharmacy (Pharm.D) students, yet research into their mental health, particularly. This study aims to fill this gap by examining the mental health of Pharm.D students in India, focusing on academic stress, peer pressure, and depression. Given the rigorous nature of pharmacy curricula and the lack of comprehensive studies in this field, assessing mental well-being among these students is essential for planning effective support initiatives and enhancing their contributions to community health.Methodology: This study invited all Pharm.D students in India to participate in an online survey assessing their mental health. The survey included demographic questions and utilized a validated scale comprising 25 items to gauge various mental health components. Data analysis was conducted using SPSS, involving descriptive statistics and inferential tests to explore correlations between mental health parameters, academic distress, and demographic variables.Results: A total of 313 Pharm.D students responded to the survey, providing insights into their demographic characteristics, academic standing, and mental health challenges. The majority of respondents were female (61%) and aged between 18-25 years (95.2%), with diverse representations across different years of study and geographic regions. Academic stress emerged as the most prevalent issue (27.5%), followed by depression (24.9%) and peer pressure (25.6%). Gender, age, year of study, and type of college exhibited varying impacts on mental health parameters, emphasizing the need for tailored interventions.Discussion: Comparison with international studies highlighted similar mental health concerns among Pharm.D students globally, with academic stress being a common challenge. Gender differences, age-related patterns, and institutional variations underscored the complex interplay of factors influencing mental wellbeing in this student population. The findings emphasize the importance of holistic support initiatives addressing academic, social, and emotional aspects of student life.Conclusion: This study provides crucial insights into the mental health landscape among Pharm.D students in India, emphasizing the pervasive nature of challenges such as academic stress, peer pressure, and depression. Urgent attention is needed to develop comprehensive support systems and enhance societal recognition for the Pharm.D profession. By addressing these issues, we can improve the overall wellbeing and academic success of Pharm.D students, contributing to a healthier pharmacy workforce. This study lays the groundwork for targeted interventions and underscores the need for further research to ensure the holistic development of pharmacy students.
Keywords: Pharm. D students; Mental health; Stress; Peer Pressure; Depression